Mapping and characterization of antigenic epitopes of arginine kinase of Scylla paramamosain. Issue 2 (June 2015) - Yang, Yang; Cao, Min-Jie; Alcocer, Marcos; Liu, Qing-Mei; Fei, Dan-Xia; Mao, Hai-Yan; Liu, Guang-Ming
Highlights The conformational epitopes and their key amino acid from Scylla paramamosain AK were identified. The linear epitopes of AK were mapped using the synthesized overlapping peptides and confirmed by cell model. The predominant epitope type of AK was defined and chemical bonds essential for the allergenicity of AK was clarified.